Reactive nitrogen, ozone and ozone production in the Arctic troposphere and the impact of stratosphere-troposphere exchange - Liang, Q.; Rodriguez, J. M.; Douglass, A. R.; Crawford, J. H.; Olson, J. R.; Apel, E.; Bian, H.; Blake, D. R.; Brune, W.; Chin, M.; Colarco, P. R.; da Silva, A.; et al. (Atmospheric Chemistry and Physics, 2011)
We use aircraft observations obtained during the Arctic Research of the Composition of the Troposphere from Aircraft and Satellites (ARCTAS) mission to examine the distributions and source attributions of O3 and NOy in the Arctic and sub-Arctic region. Using a number of marker tracers, we distinguish various air masses from the background troposphere and examine their contributions to NOx, O3, and O3 production in the Arctic troposphere. The background Arctic troposphere has a mean O3 of ~60 ppbv and NOx of ~25 pptv throughout spring and summer with CO decreasing from ~145 ppbv in spring to ~100 ppbv in summer. These observed mixing ratios are not notably different from the values measured during the 1988 ABLE-3A and the 2002 TOPSE field campaigns despite the significant changes in emissions and stratospheric ozone layer in the past two decades that influence Arctic tropospheric composition. Air masses associated with stratosphere-troposphere exchange are present throughout the mid and upper troposphere during spring and summer. These air masses, with mean O3 concentrations of 140–160 ppbv, are significant direct sources of O3 in the Arctic troposphere. In addition, air of stratospheric origin displays net O3 formation in the Arctic due to its sustainable, high NOx (75 pptv in spring and 110 pptv in summer) and NOy (~800 pptv in spring and ~1100 pptv in summer). The air masses influenced by the stratosphere sampled during ARCTAS-B also show conversion of HNO3 to PAN. This active production of PAN is the result of increased degradation of ethane in the stratosphere-troposphere mixed air mass to form CH3CHO, followed by subsequent formation of PAN under high NOx conditions. These findings imply that an adequate representation of stratospheric NOy input, in addition to stratospheric O3 influx, is essential to accurately simulate tropospheric Arctic O3, NOx and PAN in chemistry transport models. Plumes influenced by recent anthropogenic and biomass burning emissions observed during ARCTAS show highly elevated levels of hydrocarbons and NOy (mostly in the form of NOx and PAN), but do not contain O3 higher than that in the Arctic tropospheric background except some aged biomass burning plumes sampled during spring. Convection and/or lightning influences are negligible sources of O3 in the Arctic troposphere but can have significant impacts in the upper troposphere in the continental sub-Arctic during summer.